Blockchain and the future of accounting: A critical examination of promise versus practice - Ceasar, M Julias; Rajyaguru, Mihir Harishbhai; Sharma, Tushti; Devaru, Susheela Devi B; Bhosale, Yogesh H. (The International tax journal, 2025)
Blockchain has been widely promoted as a transformative technology capable of redefining financial reporting, auditing, assurance, and real-time accounting workflows. Its core attributes immutability, decentralised consensus, cryptographic verification, and distributed ledgers are frequently associated with enhanced transparency, reduced fraud, automated compliance, and audit efficiency. Yet despite strong theoretical potential, practical adoption across the accounting profession has been slow, uneven, and surrounded by technical, regulatory, organisational, and ethical barriers. This paper critically examines the gap between blockchain’s promises and its real-world implementation in accounting contexts. Drawing on emerging empirical studies, industrial applications, and regulatory insights, the paper evaluates how blockchain affects transaction recording, audit trails, asset tokenisation, smart contracts, and financial statement integrity. The findings show that while blockchain demonstrably improves traceability and internal control reliability, challenges related to scalability, interoperability, governance, data privacy, and organisational readiness significantly limit mainstream adoption. The study argues that expectations regarding blockchain’s ability to replace accountants or fully automate auditing are overstated. Instead, blockchain supports a shift toward hybrid human-AI-blockchain systems, reshaping rather than eliminating the accountant’s role. The paper concludes that blockchain’s future in accounting depends not only on technical innovation but also on regulatory clarity, ethical frameworks, and institutional adaptation.